La Salle School of Sestao Parents School (Journal of Parents and Teachers, 1996)
The School for Parents of La Salle School of Sestao promotes collaboration between family and school, emphasizing that education begins at home. It offers a training program that includes an initial course, conferences and meetings for parents and educators. It seeks an integral and effective formation to improve the educational experience of the students.
Keywords: collaboration; education; programs; training